Climbing Pinion Design for the Jacking System of a Self-elevating Platform - Ning Ren; Feng Zhou (Jixie chuandong)
The climbing pinion is an important part of the jacking system of a self-elevating platform. The key of structural design of climbing pinions is gear parameter selection and tooth shape design. Gear parameters such as large modulus， small teeth， large pressure angle and positive modification coefficient are usually selected. In tooth profile design， the influence of contact ratio and normal backlash on the normal meshing operation of climbing pinions and leg racks should be considered so as to meet the basic requirements of continuous operation of pinions and racks. After the tooth profile design is completed， three methods are used to analyze the tooth strength of climbing pinions， and a comparison is conducted. It is pointed out that the finite element method can be used as an effective method for checking the strength of large module gears.